KAJIAN NILAI TAMBAH AGROINDUSTRI OLAHAN KEDELAI MENJADI KEDELAI BUBUK DI CV. DODO-MIS MARGA ASIH KABUPATEN BANDUNG - Sintya Zahra Aulya; Dini Rochdiani (Universitas Galuh Ciamis, 2020)
Soybean is one of the important food commodities in Indonesia. Soybean consumption in Indonesia is expected to increase every year. Soybean cannot be consumed directly, but it must be processed first. The increasing consumption of soybean makes soybean processing agroindustry has a great opportunity to develop. Product from processed yellow soybean into soybean powder has the highest added value than the other products, but there are still few companies that process soybean into soybean powder. CV. Dodo-Mis is the first agroindustry that produce soybean powder especially in Bandung Regency area. The design of this study uses qualitative design and research techniques as case studies. The analysis tools used is using income analysis and value added analysis of the Hayami method. The purpose of this study was to determine the income and added value of the processing of soybeans into soybean powder.. The process of soybean processing into soybean powder at CV. Dodo-Mis is focused on 3 flavor that are natural flavor, vanila flavor, and chocolate flavor. The production process is still simple. The income of CV. Dodo-Mis from the sale of Alamina soybean powder is Rp 3.742.693 so it can be said this business is profitable with the R/C score is 1,56. The biggest added value is obtained from natural flavored soybean powder products. This is because the output of natural soybean powder is higher and natural soybean powder does not require supporting materials in the manufacturing process.